2023
DOI: 10.21037/gs-23-24
|View full text |Cite
|
Sign up to set email alerts
|

Development of a basement membrane gene signature and identification of the potential candidate therapeutic targets for pancreatic cancer

Abstract: Background: Pancreatic cancer is a deadly cancer with a poor prognosis. In light of mounting evidence that basement membrane genes (BMGs) play a role in the development of cancer, we sought to examine the prognostic importance and role of BMGs in pancreatic ductal adenocarcinoma (PDAC) patients.Methods: BMGs were obtained from previous top research studies. The clinical and messenger ribonucleic acid expression data were retrieved from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Several recent studies have already attempted to mine public databases to identify prognostic gene signatures related to BM proteins in tumors. For example, Cai et al identified a 7-gene signature associated with basement membrane proteins that predicted the prognostic status of breast cancer patients and provided insights for immunotherapy ( Cai et al, 2022 ); Zhou et al developed a risk model using 8 BMRGs, which revealed that clear-cell renal cell carcinoma patients in the low-risk group had a better response to immunotherapy ( Zhou et al, 2022 ); Lin et al established a 7-BMRG signature and identified five small compounds that could potentially be used for the treatment of pancreatic cancer patients, providing new perspectives for a deeper understanding of this disease ( Lin et al, 2023 ). Overall, these studies highlight the significance of basement membrane proteins in the precise treatment of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have already attempted to mine public databases to identify prognostic gene signatures related to BM proteins in tumors. For example, Cai et al identified a 7-gene signature associated with basement membrane proteins that predicted the prognostic status of breast cancer patients and provided insights for immunotherapy ( Cai et al, 2022 ); Zhou et al developed a risk model using 8 BMRGs, which revealed that clear-cell renal cell carcinoma patients in the low-risk group had a better response to immunotherapy ( Zhou et al, 2022 ); Lin et al established a 7-BMRG signature and identified five small compounds that could potentially be used for the treatment of pancreatic cancer patients, providing new perspectives for a deeper understanding of this disease ( Lin et al, 2023 ). Overall, these studies highlight the significance of basement membrane proteins in the precise treatment of tumors.…”
Section: Discussionmentioning
confidence: 99%